MNT2: A Longitudinal Evaluation of an Open-Source Mapping Software - Sguiglia, Fabián (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2025.13129, 2025)
El mapa no es el territorio (MNT onwards) is an open-source application developed to control synthesizers and audiovisual materials through gestures. It offers interconnectable modules providing strategies based on two-dimensional maps, which can be configured manually or using dimensionality reduction techniques. This article briefly introduces MNT2 and focuses on its evaluation process. It reviews literature on the evaluation of new musical interfaces, discussing both longitudinal and practice-based approaches. These approaches were used to design a study in which five experienced musicians and sound artists used MNT2 over several weeks, integrating it into their workflows and creative practices. Finally, the article shares the results of this evaluation.